Elite Croatian Junior Taekwondo Competitors: Morphological Characteristics and Body Composition Reference Values - Cular,Drazen (Sociedad Chilena de Anatomía, 2021)
SUMMARY: The main purpose of this study was to determine the body composition and anthropometric reference values of male and female junior Croatian taekwondo competitors according to official weight category. Additional aim of the study was to identify possible differences in variables between the weight categories. The sample comprised 247 junior participants of the national taekwondo championships divided into male (N=121) and female (N=126). The variable sample was defined by a set of 8 measurements: Body height (cm), Body mass (kg), Body mass index, Body fat (%), Body fat (kg), Muscle mass (kg), Lean body mass (kg) and Total body water (%). Results confirm previous studies proving that younger taekwondo practitioners have higher levels of body fat than their more experienced peers (seniors). Significant differences were only found between lean and heavy categories. Male junior taekwondo athletes show total body water percentages from 57.4 to 74.8 %, with significantly lower percentages in higher weight categories, while female athletes in heigher categories demonstrate a worrying level of hydration status, therefore endangering their performance and overall health. As the first paper that investigates the reference values of junior taekwondo athletes but based on official weight categories it is especially important as each weight category warrant different body composition requirements, as seen from significant differences across different variables. Future studies should include motor abilities inspection throughout the weight categories and possible use of calculation of metabolic age.